Surfactant and Neonatal Electroencephalogram - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the University of California San Diego evaluated the effects of endotracheal intubation and surfactant on the neonatal brain using a 3-channel neonatal EEG.